An Optimal Routing Strategy Based on Specifying Shortest Path - Yonghua Xu; Fei Shao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
Unlike the shortest path is randomly chosen in the traditional shortest path routing strategy, a novel routing strategy to improve the network transportation capacity is proposed in this paper. According to the different characteristics of the nodes along actual paths, we specify the shortest paths of all pairs of nodes aiming at reducing the betweenness of those high-betweenness nodes. Simulations on both computer-generated and real-world networks show that the new routing strategy can enhance the network transportation capacity greatly. And it works better in those networks with the fuzzy community structure. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.2963